SYMBIOSIS OF THEORY AND CREATIVITY: ("How are you?" – philological student conference 2017, V. Blaževska, M. Veličkovska, V. Dizdarević, S. Grujoska, M. Efremov, Skopje, Blaže Koneski Faculty of Philology, 2018) (Journal of Contemporary Philology, 2018)
Review of the Proceedings "How are you?" – philological student conference 2017, V. Blaževska, M. Veličkovska, V. Dizdarević, S. Grujoska, M. Efremov, Skopje, Blaže Koneski Faculty of Philology, 2018
Keywords: proceedings; student conference